Agharmonics: Song-Based Mnemonics on Learners’ Academic Performance in Grade 8 Science - Jan del Rosario; Life Adlin Mae Espiritu; Joey Weng Vitug; Lilibeth Fababe; Alexia Mizzy Castro (Research Synergy Foundation, 2025)
The persistent low performance of Filipino students in science, as reflected in international assessments like PISA, highlights significant challenges in science education. This study examined the effectiveness of Agharmonics, a song-based mnemonic strategy, in improving the academic performance of Grade 8 learners in science. Using a quasi-experimental design, the study involved two groups: one exposed to traditional instruction and another taught using validated song-based mnemonics. Researcher-made pre-tests and post-tests were administered, and statistical analyses, including paired and independent t-tests, were used to measure academic gains and compare group performances. Results revealed that both groups started at comparable proficiency levels, but the experimental group demonstrated a significantly higher post-test mean score (M = 26.25) compared to the control group (M = 20.19). A highly significant difference (p < .001) was observed within the experimental group’s pre- and post-test scores, indicating the effectiveness of the strategy. Learners reported enhanced retention and engagement, particularly in mastering abstract scientific concepts. Findings suggest that Agharmonics is an effective and engaging instructional approach that may be applied more broadly to improve science education outcomes. The study recommends integrating music-based strategies in teaching and further research on their long-term effects across various educational contexts.